Study of the radioactivity in environmental soil samples from Eastern Anatolia Region of Turkey - Ş, Turhan; Gören E.; Ugur F.A.; Karataşll M.; Yegingil Z. (Walter de Gruyter GmbH, 2017)
Abstract In this study, a detailed γ-ray spectrometer survey was performed to obtain the baseline data on natural and fallout radioactivity in soil samples (10–30 cm depth) collected from Iğdır which is a province in Eastern Anatolia Region of Turkey and located along the border with Armenia. Metsamor Nuclear Power Plant in Eastern Armenia is only about 20 km away from Iğdır province. The average activity concentrations of 226Ra, 232Th, 40K and 137Cs in the soil samples were found as 19.1±0.6 (range: 12.8–31.2 Bq kg−1), 21.9±0.6 (range: 11.6–36.8 Bq kg−1), 437.7±10.3 (range: 285.0–613.7 Bq kg−1) and 11.8±1.1 Bq kg−1, (range: 2.5–51.1 Bq kg−1), respectively. The radiological hazards caused by ionizing radiation emitted from these radionuclides on the population living in the region were assessed by estimating radiological parameters such as absorbed γ dose rate in outdoor and the corresponding annual effective dose rate from external exposure, annual effective dose rate from inhalation of radon and excess lifetime cancer risk. The results revealed that there is no significant radiological hazard for human population because the average values of radiological parameters are within the recommended limits.
Keywords: Soil; Cs; natural radioactivity; radon; excess lifetime cancer risk; annual effective dose; outdoor dose rate; ?-ray spectrometer; 13. Climate action; 7. Clean energy